KOMPETENSI KOMUNIKASI ANTAR PRIBADI DALAM PROSES PENGUATAN HUBUNGAN SUAMI ISTRI BEKERJA - Lestari, Sri Budi (JURNAL ILMU SOSIAL, 2007)
Communication competence in a family whose parent were working, in the reality cn give one agreement concerning role which they run. There are some changes of role, especially at role of children education, nowadays, not only predominated by a mother. In this reseach,was also found that children togetherness, in fact, their time is much more with his father rather than their mother, because of their father’s flexibility time to work.